Effects of Modified Pilates on Incontinence Severity and Quality of Life in Females with Urinary Incontinence - Masooma Saleem, Zainab Hassan, Azfar Khurshid, Maryam Khalid, Waqas Latif (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Urinary Incontinence is a state in which an individual is unable to control urine and may leak it out without reaching to the toilet. The urgency of urine becomes out of control in such patients. Aim: To determine the effects of modified Pilates on incontinence severity and quality of life in females with urinary incontinence. Study Design: Randomized Controlled Trial. Methodology: Patients (n=50) were analyzed. The Group A received modified Pilates along with standard physical therapy while group B received standard physical therapy exercises only. Baseline treatment that was standard physical therapy (pelvic floor muscle training, home exercises plan and life style advice) was given to both groups. Outcome measures were calculated by Symptom Severity Index and Incontinence Quality of Life questionnaire. Results: The mean value of Symptoms Severity Index score of group A before intervention was 21.04 which was more than 16.04, the value obtained after the treatment. This value was less than the post Symptoms Severity Index mean of group B (standard physical therapy only). The Symptoms Severity Index score between both groups has massive difference with P value <0.05. Conclusion: It was concluded that modified Pilates combined with standard physical therapy improves urinary incontinence severity and quality of life in females with urinary incontinence. Keywords: Modified Pilates, Quality of Life, Standard Physical Therapy and Urinary Incontinence.